PENDIDIKAN MORAL DALAM MULTI PERSPEKTIF - Zuhairansyah Arifin (Lembaga penelitian dan pengabdian kepada Masyarakat, 2011)
Education and moral are two words not be separated. We can say that education is speak about morality, but in the other side, the good moral must be resulted by education. Philosophy of moral can to appear with human life to choose much of methods to formulation the good morality in life. It implication developed by realizing the good methods around teacher, lectures, and students. At last, developing of values can to arising plurality of moral. The plurality can to arise behavior where in one of man, morality is good, but in othe men morality is not good. But we can say, that moral values are absolutely, it mean; the morality certainly have the permanent character. But in other men that moral values are relatively, can be grow different/inconstant. Those different, especially for human life that have religious/moslem, must be attitude with intellect or prudent by values of al-Qur’an.